Pertanggung Jawaban Hukum Bagi Pelaku Usaha Jual Beli Online yang Mengakibatkan Kerugian Konsumen Ditinjau dari Undang-Undang Nomor 19 Tahun 2016 dan Undang-Undang Nomor 8 Tahun 1999.: Legal Responsibility for Online Buying and Selling Business Actors Who Cause Consumer Losses Reviewed from Law Number 19 of 2016 and Law Number 8 of 1999. - Revi Mariska Siregar; M. Hendra Pratama Ginting (Information Technology and Science (ITScience), 2026)
The Indonesian government passed Law Number 11 of 2008 concerning Electronic Information and Transactions, which was later amended to Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Electronic Information and Transactions. The amendments focused on Articles 27, 28, and 29, which were previously considered open to multiple interpretations and therefore needed to be clarified to provide legal certainty for internet users and improve consumer protection in online buying and selling transactions. This study uses a normative juridical research type because it focuses on the study of applicable legal regulations in legislation. The approach used is a statute approach, namely by examining various laws and regulations related to the legal issues being studied. The research data uses secondary data obtained through literature studies, which were then analyzed using qualitative analysis methods. The results of the study indicate that the implementation of Law Number 8 of 1999 concerning Consumer Protection, together with the ITE Law, has provided a fairly strong legal basis for taking action against business actors who harm consumers through electronic transactions. However, business actors' low awareness of the importance of consumer protection often leads to the neglect of consumer rights, such as the obligation to provide accurate and transparent information, guarantee product quality, and responsibility for losses suffered by consumers. Therefore, business actors have a legal obligation to protect consumer rights and can be held accountable if proven to have committed negligence, fraud, or violations in electronic transaction systems.